Can nurture alter nature? The effects of a parenting intervention program on reducing antisocial behaviors - Mohajeri-Nelson, Nazanin, author; MacPhee, David L., advisor; Canetto, Silvia S., advisor; Cross, Jennifer E., committee member; Deffenbacher, Jerry L., committee member; Swaim, Randall C., committee member (Colorado State University. Libraries, 2006)
Multiple correlates of antisocial behaviors, ranging from genetic and biological factors (such as temperament) to environmental influences (such as parenting), have been implicated in previous research. Most contemporary researchers recognize an interactive relationship between the innate and environmental influences. However, the causal relationship between nature and nurture, and how they interact to shape behavior, is still being debated. Some researchers have argued for the minimal role of environmental influences, specifically parenting, while others have found stronger evidence for the effects of parenting. For example, some researchers have concluded that child characteristics elicit varying types of parenting, speculating that any differences in parenting practices can be better explained by differences in children's behavior than vice versa. Conversely, other researchers have concluded that one of the primary influences on the development of antisocial behaviors is parenting practices, particularly harsh parenting. The purpose of the current study was to test the influence of one environmental factor, parenting, on the development of antisocial behaviors, including oppositional behaviors and overall problematic behaviors, and to test any causal link between parenting and those antisocial behaviors. The impact of parenting on antisocial behaviors was analyzed with a longitudinal intervention program targeting families with children between the ages of 2 - 6 at-risk for higher rates of delinquency, oppositional behaviors, and substance use. The intervention program altered parenting practices and reduced problematic behaviors. Because of the correlations between punitive parenting practices and children's antisocial behaviors, decreased use of punitive child-rearing practices was expected to result in lower levels of oppositional and problematic behaviors. In order to determine if the changes in parenting practices mediated the effects of the intervention, a parallel process latent growth curve model was utilized to determine whether the rate of change in parenting practices impacted the rate of change in oppositional and problematic behaviors. The hypotheses were partially supported. Only one of the parenting variables, harsh and authoritarian composite score, mediated the effects of the intervention on children's oppositional and problematic behaviors.
Keywords: developmental psychology; families and family life; personal relationships; sociology; individual and family studies